HUBUNGAN KEMAMPUAN TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE ( TPACK ) GURU TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN GEOGRAFI PADA MATERI FASE F DI SMAN 7 PADANG - Budi Hermawan, Aditya; Anwar, Syafri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking skills are essential competencies that must be possessed by senior high school students in the 21st century, as students are required to think deeply, reflectively, and logically. Therefore, the development of students critical thinking skills also requires strong instructional competence from teachers. This study aims to examine the relationship between teachers TPACK and students critical thinking skills in geography learning. This study employed a quantitative method with a correlational design. The sampling technique used was purposive sampling, involving students from classes XI F 6 and XI F 11 as the research samples. Teachers TPACK was measured using a questionnaire based on TPACK indicators proposed by Mishra, Koehler, Schmid, Chai, Koh, and Tsai, which include ( Content Knowledge, Pedagogical Knowledge, Technological Knowledge, Pedagogical Content Knowledge, Technological Content Knowledge, Technological Pedagogical Knowledge, and Technological Pedagogical Content Knowledge ). Students critical thinking skills were measured using an objective test based on critical thinking indicators proposed by Peter A. Facione, namely ( interpretation, analysis, evaluation, inference, and explanation )The data were analyzed using SPSS version 29 and descriptive analysis. The data analysis techniques included normality testing and hypothesis testing. The results of the statistical analysis using the Spearman correlation test with the assistance of SPSS version 29 showed a significance value of 0.001 < 0.050. These results indicate that there is a significant relationship between teachers’ TPACK and students’ critical thinking skills. The correlation coefficient value of 0.794 indicates a very strong relationship between TPACK and students’ critical thinking skills. Keywords: TPACK, Critical Thinking, Correlational Study